Evaluation and comparison of white mineral trioxide aggregate and formocresol medicaments in primary tooth pulpotomy: Clinical and radiographic study - Cheranjeevi Jayam; Malay Mitra; Jiban Mishra; Bhaswar Bhattacharya; Biswanath Jana (Wolters Kluwer Medknow Publications, 2014)
Aim: The primary aim of the following study is to evaluate and secondary aim is to compare clinically and radiographically the success of using white mineral trioxide aggregate (MTA) versus formocresol (FC) medicament for primary tooth pulpotomy. Materials and Methods: A total of 100 teeth were selected for pulpotomy; of which 50 teeth underwent FC pulpotomy and 50 teeth underwent pulpotomy with white MTA. Out of 100 treated teeth, 82 teeth (42 FC and 40 MTA teeth) were available at the end of 24 months for evaluation. 4 failures were found in FC group at 1 st month evaluation and no failures were found in white MTA group. A statistical analysis was performed to evaluate the overall success rate of study and individual success rates of medicaments. Overall success rate of the study was 95%, success rate of FC group was 90.48% and success rate of MTA group was 100%. Results: MTA produced better results as pulpotomy medicament in comparison to FC. The superior success obtained in the present study was matching other studies mentioned in the literature. Conclusion: MTA seems to be a promising pulpotomy medicament for future use.